RESULTS OF PETROPHYSICAL STUDIES OF THE PRODUCTIVE STRATUM DEPOSITS OF THE BAKU ARCHIPELAGO NORTHERN OIL AND GAS BEARING AREAS - Gurbanov, V.; Sultanov, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The complex results of petrophysical testing of rocks, taken from prospecting-development wells of Duvanni-deniz, Sangachal-deniz, Bulla-deniz, Garasu and etc. areas, where the sediments of productive stratum are widely expanded, have been given. Average values of granulometric composition of rocks of productive unit of the above areas by the section have been recounted. The problem of dependence of permeability on porosity and depth was solved. Dependence between physical parameters for the individual kinds of rocks, dependence between physical properties and material structures are established. The results of various petrophysical research methods show that the filtration capacitance properties, in general, deteriorate with depth. However, in certain cases, in clay and carbonate rocks, reservoir properties can improve, due to the appearance of secondary porosity under relatively stringent thermobaric conditions. The histograms, which consist of average values of granulometric composition of productive stratum rocks when crossing some places of archipelago are constructed, the problems of dependence of permeability on porosity and depth were solved. The researches showed, that the physical process of the same- named and same-aged features rocks change in the result of geological-physical processes, getting different values. It’s noticed, that the porosity and permeability are increasing from north-west to south-east by changing lithological composition.